The Effect of Giving Eco Enzyme Based on Dayak Onion (Eleutherine palmifolia Merr.) in Drinking Water on the Lymphoid Organs of Broilers - Osseta, Amelia; Fati, Nelzi; Nilawati, Nilawati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
This study aims to determine the effect of administering eco enzyme based on Dayak onions (Eleutherine palmifolia Merr.) on broiler lymphoid organs including bursa fabricius, spleen and thymus. The design used was a completely randomized design consisting of 5 treatments and 4 replications. There are 100 broilers aged 1 day to 35 days. Each test consists of 40 animals. Treatments were: A0= without addition of Dayak onion eco enzyme, A1= addition of 1% Dayak onion eco enzyme, A2= addition of 1.5% Dayak onion eco enzyme, A3= addition of 2% Dayak onion eco enzyme, A4= addition of 2.5 % eco enzyme Dayak onion. The variables observed were the bursa of Fabricius, spleen and thymus. The results of the research showed that the addition of eco enzyme based on Dayak onions had no significant effect (P>0.05) on the percentage of bursa fabricius, spleen and thymus. The conclusion of this research is that the addition of Dayak onion-based eco enzyme at different levels does not have a significant effect on broiler lymphoid organs. The addition of up to 2.5% in drinking water can still be tolerated by broilers.